Analisis Prediksi Gempa Bumi Menggunakan Algoritma Decision Tree C4.5: Studi Literatur - Ahmad Heriansyah; Hetty Rohayani (JOURNAL VISION TECHNOLOGY (V-TECH), 2026)
Earthquakes are natural disasters that can severely affect human lives and infrastructure. This study aims to analyze and evaluate the effectiveness of the C4.5 decision tree algorithm in predicting earthquakes based on historical seismic data. Using a quantitative approach and systematic literature review, the study compiles information from previous research related to earthquake prediction models. The results suggest that the C4.5 model provides reasonably high prediction accuracy in earthquake-prone areas and could be integrated into early warning systems.